Position-sensitive gaseous photomultipliers research and applications - Francke, Tom 1964-; Peskov, Vladimir (Advances in chemical and materials engineering (ACME) book series, 2016)
This book explores the advancement of gaseous detectors as applied for single photon detection, emphasizing emerging perspectives and new ways to apply gaseous detectors across research fields